2018
DOI: 10.3122/jabfm.2018.04.170388
|View full text |Cite
|
Sign up to set email alerts
|

How Evolving United States Payment Models Influence Primary Care and Its Impact on the Quadruple Aim

Abstract: Introduction: Prior research has demonstrated the associations between a strong primary care foundation with improved Quadruple Aim outcomes. The prevailing fee-for-service payment system in the United States reinforces the volume of services over value-based care, thereby devaluing primary care, and obstructing the health care system from attaining the Quadruple Aim. By supporting a shift from volume-based to value-based payment models, the Medicare Access and Children's Health Insurance Program Reauthorizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
0
18
0
1
Order By: Relevance
“…Eijkenaar [67], Park et al [68], and Conrad [69] presented some characteristics that they found to be linked to the success of monetary incentive systems. Figure 2 lists the success factors for those reimbursement mechanisms dealt with in this review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eijkenaar [67], Park et al [68], and Conrad [69] presented some characteristics that they found to be linked to the success of monetary incentive systems. Figure 2 lists the success factors for those reimbursement mechanisms dealt with in this review.…”
Section: Discussionmentioning
confidence: 99%
“…
Fig. 2 Success factors for different reimbursement schemes found by Eijkenaar [ 67 ], Park et al [ 68 ], and Conrad [ 69 ]. FFS fee for service
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe such questions, spurred by the examples of the 3 pioneer practices, have potential to open a new frontier in the science of dissemination and implementation and inform better health policy. 55…”
Section: Future Directionsmentioning
confidence: 99%
“…In a thought piece, Park et al 4 conclude that current U.S. payment models do not adequately support the primary care infrastructure known to improve outcomes, that is, team-based community-oriented care that measures the delivery of the functions of primary care.…”
Section: Health System and Family Medicinementioning
confidence: 99%